Heterocyclic Surgery for Isotopic Labeling - Smith, Joel M. (Synlett, 2024)
Recent developments in the isotopic labeling of heteroarenes may prove to be useful in the realms of biomedical science, materials chemistry, and fundamental organic chemistry. The use of the age-old Zincke reaction, or tactical variants thereof, has become particularly utilitarian in effecting single-atom nitrogen replacement in various azines to generate their desired isotopologues. This chemistry can be synthetically leveraged at an early stage for diversity-oriented heterocyclic labeling of pharmaceuticals and/or natural products. Additionally, given the prevalence of saturated azacycles in biologically relevant molecules, access to these isotopologues becomes relevant through dearomative retrosynthetic analysis from the corresponding 15N-labeled heteroarenes.1 Introduction2 Our Lab’s Development of the 15NRORC Reaction3 Other Recent Azine-Labeling Methods4 Expanded ANRORC Utilization5 Conclusion and Outlook
Keywords: pyridine; azine; isotope; labeling; Zincke; dearomatization; ANRORC